Streptococcus pneumoniae galU gene mutation has a direct effect on biofilm growth, adherence and phagocytosis in vitro and pathogenicity in vivo. Issue 7 (24th August 2018) - Cools, F; Torfs, E; Vanhoutte, B; de Macedo, M Bidart; Bonofiglio, L; Mollerach, M; Maes, L; Caljon, G; Delputte, P; Cappoen, D; Cos, P
Abstract: Streptococcus pneumoniae, the most common cause of bacterial pneumonia, has developed a wide range of virulence factors to evade the immune system of which the polysaccharide capsule is the most important one. Formation of this capsule is dependent on the cps gene locus, but also involves other genes—like galU . The pyrophosphorylase encoded by galU plays a role in the UDP-glucose metabolism of prokaryotes and is required for the biosynthesis of capsular polysaccharides. In this paper, the effect of a galU mutation leading to a dysfunctional UDP-glucose pyrophosphorylase (UDPG:PP) on in vitro biofilm biomass, adherence to lung epithelial cells and macrophage phagocytosis is studied. Last, in vivo virulence using a Galleria mellonella model has been studied. We show that the mutation improves streptococcal adherence to epithelial cells and macrophage phagocytosis in vitro, while there is no definitive correlation on biofilm formation between parent and mutant strains. Moreover, in vivo virulence is attenuated for all mutated strains. Together, these results demonstrate that a galU mutation in S. pneumoniae influences host cell interactions in vitro and in vivo and can strongly influence the outcome of a streptococcal infection. As such, UDPG:PP is worth investigating further as a potential drug target. Abstract : Mutation of the galU gene has an influence on in vitro interactions with immune cells and in vivo streptococcal pathogenicity using a Galleria mellonella infection model.